Chinook salmon diversity contributes to fishery stability and trade‐offs with mixed‐stock harvest. Issue 8 (21st September 2022) - Connors, Brendan M.; Siegle, Matthew R.; Harding, Joel; Rossi, Steven; Staton, Benjamin A.; Jones, Michael L.; Bradford, Michael J.; Brown, Randy; Bechtol, Bill; Doherty, Beau; Cox, Sean; Sutherland, Ben J. G.
Abstract: Variation among populations in life history and intrinsic population characteristics (i.e., population diversity) helps maintain resilience to environmental change and dampen interannual variability in ecosystem services. As a result, ecological variation, and the processes that generate it, is considered central to strategies for managing risks to ecosystems in an increasingly variable and uncertain world. However, characterizing population diversity is difficult, particularly in large and remote regions, which often prevents its formal consideration in management advice. We combined genetic stock identification of archived scale and tissue samples with state‐space run‐reconstruction models to estimate migration timing and annual return abundance for eight geographically and genetically distinct Chinook salmon populations within the Canadian portion of the Yukon River. We found that among‐population variation in migration timing and return abundances resulted in aggregate return migrations that were 2.1 times longer and 1.4 times more stable than if they had composed a single homogeneous population. We then fit state‐space spawner–recruitment models to the annual return abundances to characterize among‐population diversity in intrinsic productivity and population size and their consequences for the fisheries they support. Productivity and carrying capacity varied among populations by approximately 2.4‐fold (2.9 to 6.9 recruits per spawner) and three‐fold (8800 to 27, 000 spawners), respectively. This diversity implies an equilibrium trade‐off between harvesting of the population aggregate and the conservation of individual populations whereby the harvest rate predicted to maximize aggregate harvests comes at the cost of overfishing ~40% of the populations but with a relatively low risk of extirpating the weakest ones. Our findings illustrate how population diversity in one of the largest salmon‐producing river basins in the world contributes to fishery stability and food security in a region where salmon have high cultural and subsistence value. More generally, our work demonstrates the utility of molecular analyses of archived biological material for characterizing diversity in biological systems and its benefits and consequences for trade‐offs in decision‐making.